Health-related quality of life in children and adolescents with tuberous sclerosis complex and their caregivers: A multicentre cohort study from Germany. (November 2021) - Willems, Laurent M.; Schubert-Bast, Susanne; Grau, Janina; Hertzberg, Christoph; Kurlemann, Gerhard; Wiemer-Kruel, Adelheid; Bast, Thomas; Bertsche, Astrid; Bettendorf, Ulrich; Fiedler, Barbara; Hahn, Andreas; Hartmann, Hans; et al.
Abstract: Objective: This study aimed to measure health-related quality of life (HRQOL) in children and adolescents with tuberous sclerosis complex (TSC) and quality of life (QOL) and depressive symptoms among caregivers. Methods: Adequate metrics were used to assess HRQOL in children and adolescents with TSC (4–18 years, KINDL R ) as well as QOL (EQ-5D) and symptoms of depression (BDI-II) among caregivers. Predictors for reduced HRQOL and depressive symptoms were identified by variance analysis, ordinal regression, and bivariate correlation. Results: The mean HRQOL score was 67.9 ± 12.7, and significantly lower values were associated with increasing age, attending special needs education, TSC-associated psychiatric symptoms, and drug-related adverse events. The mean QOL of caregivers was 85.4 ± 15.7, and caregiver's sex, TSC mutation locus, familial TSC clustering, special needs education, degree of disability, care dependency, presence of TSC-associated psychiatric symptoms, and TSC severity were significant predictors of lower QOL. Depressive symptoms were identified in 45.7% of caregivers, associated with female sex of the caregiver, familial TSC clustering, special needs education, and presence of TSC-associated psychiatric symptoms of the child. Multivariate regression analysis revealed adolescence and drug-related adverse events as significant predictors for lower HRQOL in TSC children, and TSC2 variants predicted lower QOL and depressive symptoms in caregivers. Conclusion: Compared with other chronic diseases, such as headache, diabetes or obesity, children with TSC have significantly lower HRQOL, which further decreases during adolescence. A decreased HRQOL of patients correlates with a lower QOL and increased symptoms of depression of their caregivers. These results may improve the comprehensive therapy and care of children and adolescents with TSC and their families and caregivers. Trial registration: DRKS, DRKS00016045. Registered 01 March 2019, http://www.drks.de/DRKS00016045 . Highlights: Multicenter study in 184 children with TSC as well as their caregivers Children with TSC have significantly lower HRQOL than the normal population Adolescence, drug-related adverse events and the severity of TSC manifestation impact HRQOL Caregivers have lower QOL and more depressive symptoms than the normal population TSC2 variants were predictive of lower QOL and increased depressive symptoms in caregivers